Correction: Comparative efficacy of 0.1% and 0.15% Sodium Hyaluronate on lipid layer and meibomian glands following cataract surgery: A randomized prospective study. - Seung Ahn Yang; Mu Ryang Jeong; Cheon Ho Park; Ki Bum Cheon; Jun Ho Chang; Ji Eun Lee (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0306253.].